تعريف المتطلبات الأولية الضرورية لتطوير نظام التسجيل العقاري في سورية - زوباري, علي عز الدّين; يحيـى, منيـر داؤد (Latakia University Journal -Engineering Sciences Series, 2019)
إن الهدف الرئيس من هذا البحث هو تعريف المتطلبات الأولية الضرورية لتطوير نظام التسجيل العقاري نحو نظام معلومات عقاري مؤتمت، ولتحقيق هذا الهدف، تم إجراء دراسة ميدانية في مديرية المصالح العقارية باللاذقية، فقد تم دراسة الواقع الفعلي لنظام التسجيل العقاري الحالي وتحليله واكتشاف خصائصه ومزاياه وعيوبه، ومن ثم تحديد الوظائف والمهام التي يجب أن ينفذها مستقبلاً, والبيانات التي سوف يحتاجها والخدمات التي سوف يقدمها، والتشاركية مع الجهات الأخرى. بوصفها ثمرة لهذه الدراسة، تم استنتاج أن نظام التسجيل العقاري الحالي له بعض الإيجابيات، لكن أهم ما يميزه هو أنه يؤمن حقوق الحماية (الثقة والأمن للملكية). ومن جهة أخرى فإن السلبيات والعيوب كثيرة. وقد تم من خلالها صياغة عدة توصيات شاملة وتصنيفها ضمن مجموعة متطلبات يجب أخذها بعين الاعتبار بشكل أساسي لتطوير نظام التسجيل العقاري الحالي نحو نظام معلومات عقاري حديث. وهذه المتطلبات هي: المتطلبات القانونية، والمتطلبات التقنية، والمتطلبات التنظيمية، والمتطلبات المؤسساتية، ومتطلبات المهام والوظائف، بالإضافة إلى متطلبات الكفاءات والخبرات. This research aims at defining the primary requirements needed for developing the present form of cadastral system in Syria toward a modern cadastral information system. In order to perform this research, a practical study was conducted at the cadastral directorate in Latakia. The actual performance of the present form of cadastral system was investigated and analyzed; its properties, advantages and faults were detected. Subsequently, the main functions and jobs to be achieved; the needed data, and services that will be provided in future were determined; Also the partnership with other management directions were studied. As a result of this research, we can conclude that the present cadastral system has some advantages; the unique one is that the functions and tasks are achieved carefully with high-reliability. On the other side, many disadvantages and faults were determined. So that, many recommendations were suggested and classified into many primary requirements that need to be considered, such as legal, technical, organizational, institutional, and other necessary requirements related to functions, jobs, experiences and qualifications.